Prevalence of Hepatitis E Virus Antibodies, Israel, 2009–2010 - Orna Mor; Ravit Bassal; Michal Michaeli; Marina Wax; Daniela Ram; Oranit Cohen-Ezra; Dani Cohen; Ella Mendelson; Ziv Ben-Ari; Tamy Shohat (Emerging Infectious Diseases, 2015)
We investigated prevalence of hepatitis E virus in a sample of the population of Israel. The overall seroprevalence of antibodies to the virus was 10.6% (95% CI 8.4%–13.0%); age-adjusted prevalence was 7.6%. Seropositivity was associated with age, Arab ethnicity, low socioeconomic status, and birth in Africa, Asia, or the former Soviet Union.